2019
DOI: 10.1038/s41598-019-42140-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of optical nonlinearity of photo-responsive liquid crystals revealed by transient grating imaging

Abstract: A large optical nonlinearity has been observed for the photo-responsive liquid crystals under the condition that the nematic phase is close to the isotropic condition. The direct observation of the photo-response of a liquid crystal by the time-resolved transient grating phase imaging technique revealed that the optical nonlinearity was caused by the transiently generated phase formed inside the photo-induced isotropic region. A shock-like flow was observed for the formation of the transiently generated phase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This method was successfully applied to observe millisecond dynamics in photo-responsive liquid crystals. 88 However, in our research, 25 we discovered that the image quality achieved with Talbot self-imaging was almost same level as that of Schlieren imaging. In Talbot self-imaging, the image is slightly defocused by a few microns to transition the phase image into an amplitude image, yielding a spatial resolution of about 3 mm in our optical setup.…”
Section: Defocus Induced Phase-contrast Image Enhancement and Fast Im...mentioning
confidence: 55%
See 1 more Smart Citation
“…This method was successfully applied to observe millisecond dynamics in photo-responsive liquid crystals. 88 However, in our research, 25 we discovered that the image quality achieved with Talbot self-imaging was almost same level as that of Schlieren imaging. In Talbot self-imaging, the image is slightly defocused by a few microns to transition the phase image into an amplitude image, yielding a spatial resolution of about 3 mm in our optical setup.…”
Section: Defocus Induced Phase-contrast Image Enhancement and Fast Im...mentioning
confidence: 55%
“…To demonstrate the measurement technique, a stripe pattern identical to the transient grating excitation was used. 88…”
Section: Analysis and Equipmentmentioning
confidence: 99%
“…TGS with nanosecond and microsecond resolutions is naturally suitable for investigating dynamics in soft matter and biological materials. A recent example utilized TGS coupled with imaging to probe the photo-induced flow and phase transition in a liquid crystal [113].…”
Section: Discussionmentioning
confidence: 99%
“…The principle of the PI-PM method was described in previous papers and is shown in Figure S1 in Supporting Information (SI) [ 38 , 39 ]. In brief, an arbitrary pump light pattern is irradiated to a sample, causing photoisomerization and the following molecular rotation and disordering for the LCs.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…In recent years, we have studied the origin of the optical nonlinearity from the dynamics of the LCs by using time-resolved methods and found that the enhancement occurred on the millisecond time scale [ 37 ]. Furthermore, a new time-resolved imaging technique was developed, and the origin was clarified by visualizing the images of the optically induced flow of the LCs [ 38 ].…”
Section: Introductionmentioning
confidence: 99%